The Effect of Leverage, Efficiency, and Accounting Profit on Profitability at PT Adhi Karya (Persero) Tbk Period 2015-2024 - Kiki Anggar Wati; Vidya Amalia Rismanty (Indonesian Economic Review, 2026)
This study analyzes the influence of leverage, asset efficiency, and accounting profit on profitability measured by Return on Equity (ROE) at PT Adhi Karya (Persero) Tbk during 2015–2024. Leverage is proxied by the Debt to Equity Ratio (DER), efficiency by Total Asset Turnover (TATO), and accounting profit by earnings before tax. This research applies a quantitative explanatory method using secondary data derived from published annual financial statements. Data were analyzed using multiple linear regression with classical assumption tests including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results indicate that partially, leverage and efficiency do not significantly affect profitability, while accounting profit has a positive and significant effect on ROE. Simultaneously, the three independent variables significantly influence profitability. The Adjusted R² value of 0.895 shows that 89% of profitability variation is explained by the model. These findings suggest that profit stability plays a more dominant role in improving shareholder returns compared to capital structure and asset utilization alone.